Factors Associated with Medical Waste Management at Haji Saeful Anwar General Hospital in Pagaden, Subang Regency, in 2026 - Muslimin; Rokhmatul Hikhmat; Teten Rustendi; Muhidin; Warsa Agung Nugraha (Riviera Publishing, 2026)
The results of a preliminary study conducted on February 20, 2026, in the field, including observations and interviews with the sanitation department, revealed dissatisfaction among nurses and sanitation staff regarding medical waste management at Haji Saeful Anwar Pagaden General Hospital, Subang Regency. The purpose of this study was to determine factors related to medical waste management at Haji Saeful Anwar Pagaden General Hospital, Subang Regency, in 2026. The study used a descriptive analytical method with a cross-sectional design. The population in this study consisted of all 74 nurses and sanitation staff at Haji Saeful Anwar Pagaden General Hospital, Subang Regency. The sampling technique employed was total sampling, using bivariate and univariate analysis of the independent and dependent variables, with a questionnaire as the data collection instrument. The results of the study showed that of the 74 respondents, the majority (58 respondents, 78.4%) had good knowledge of medical waste management; the majority (69 respondents, 72.2%) had good attitudes toward medical waste management; the majority (65 respondents, 87.8%) had good infrastructure for medical waste management; the majority (65 respondents) implemented the rules properly for medical waste management; and the majority (55 respondents) had good supervision of medical waste management. Statistically, the relationship between the variables of medical waste management factors and medical waste management implementation showed a significant association, with a Chi-Square test result of 10.503 and ? < 0.05, yielding a P-value of 0.00.